Investigating Toefl iBT Writing Tasks (A Case-Study of EFL Learners) - Nurhayati S.; Rahmi Aulia Nurdini (ITScience (Information Technology and Science), 2022)
According to (Sharpe, Orientation to the TOEFL iBT, 2019), the TOEFL iBT assesses the test-taker’s ability to understand and use English for academic purposes. The TOEFL has four sections: listening, reading, speaking, and writing, each with its own set of instructions. The writing section assesses test-takers' ability to write essays in English. They write one essay about an academic topic (integrated task) and one essay about a familiar topic during the test (independent task). The academic essay requires them to relate information from a reading passage to information from a listening passage. The researchers conducted a similar study to learn about EFL learners' challenges when taking the test to improve TOEFL iBT writing instruction strategies. This study aims to investigate the errors and to discover if there are any new findings, as diverse techniques are found in participants' writing tasks, which could provide more general information for researchers and readers. The results showed that the typical grammar errors were almost in line with the previous studies. Another comparison was that Khoshkou and Keyvanfar did not provide missed information and conclusion insertions as other typical mistakes in the integrated task. However, the other errors—plagiarism, adding one's ideas, and question-addressing—are consistent with the study's findings. It suggests the researchers, as TOEFL iBT tutors, emphasize paraphrasing techniques and for participants with weaker English proficiency need more practice time to advance.